An osteological study of measurement of safe zone to prevent iatrogenic suprascapular nerve injury and its correlation with type of suprascapular notch - Hafezji, Hamzah M. (International Journal of Research in Medical Sciences, 2016)
Background: Suprascapular nerve injury is commonly recognized as a cause of post-operative shoulder pain and rotator muscle dysfunction. The nerve may be injured during open or arthroscopic shoulder surgeries, due to its proximity to the operative field, particularly at the suprascapular and spinoglenoid notches. ‘Safe zone’ is defined as an area within which iatrogenic injury to the suprascapular nerve is likely to be avoided and it presents definitive limits. Aims of study were to identify morphometric variations of suprascapular notch (SSN), to measure distances from commonly used surgical landmarks to the possible course of suprascapular nerve so as to identify safe zone and to correlate safe zone with the type of suprascapular notch (SSN). Methods: Total 200 dry human scapulae were obtained from Anatomy departments of three medical colleges of south Gujarat. Using digital vernier caliper, for each SSN, maximal depth (MD) and superior transverse diameters (STD) were measured and SSN classified into five types. The distances of suprascapular nerve from common surgical landmarks were measured as ‘AB’; ‘CD’ and ‘BD’ to obtain safe zone. These distances were correlated with dimension of notch. Results of the present study were compared with previous studies in different populations. Results: The suprascapular notch was classified into five types of which Type III (MD <STD) predominate (46.5%). The mean measurements of ‘safe zone’ distances vary with type of notch and correlate with notch dimensions. Conclusions: The precise knowledge of morphology in the shoulder girdle region (especially, variations of SSN) is particularly essential to avoid iatrogenic nerve injuries during shoulder surgeries. The measurements of ‘safe zone’ help clinicians for safe advancement during surgeries. The safe zone varies with the type of suprascapular notch.